Determinants of Corporate Social Responsibility Disclosure: Evidence in Pharmaceutical Company Listed in The Indonesian Sharia Stock Index - Al Arif, Mohammad Nur Rianto; Dhofir, M. Alfan Haidar (El-Qish: Journal of Islamic Economics, 2023)
There are several factors that are thought to influence the disclosure of corporate social responsibility including profitability, debt, and company size. However, based on previous research found inconsistent results related to the effect of these variables on the disclosure of corporate social responsibility. This study aims to determine the partial and simultaneous effect of profitability, debt and company size variables on the disclosure of social responsibility of 8 pharmaceutical companies listed on Indonesian Sharia Stock Index. The analysis technique of this study uses panel data regression with the Fixed Effect Model. Findings. The results of the study show that partially the firm size variable has an effect on disclosure. These results implies that in accordance with the legitimacy theory that large companies have more activities and wider impact.